Hereditary intrinsic factor deficiency in China caused by a novel mutation in the intrinsic factor gene-a case report - Jing Ruan; Bing Han; Junling Zhuang; Miao Chen; Fangfei Chen; Yuzhou Huang; Wenzhe Zhou (BMC, 2020)
Abstract Background Hereditary intrinsic factor deficiency is a rare disease characterized by cobalamin deficiency with the lack of gastric intrinsic factor because of gastric intrinsic factor (GIF) mutations. Patients usually present with cobalamin deficiency without gastroscopy abnormality and intrinsic factor antibodies. Case presentation A Chinese patient presented with recurrent severe anemia since age 2 with low cobalamin level and a mild elevation of indirect bilirubin. The hemoglobin level normalized each time after intramuscular vitamin B12 injection. Gene test verified a c.776delA frame shift mutation in exon 6 combined with c.585C > A nonsense early termination mutation in exon 5 of GIF which result in the dysfunction of gastric intrinsic factor protein. The hereditary intrinsic factor deficiency in literature was further reviewed and the ancestry of different mutation sites were discussed. Conclusions A novel compound heterozygous mutation of GIF in a Chinese patient of hereditary intrinsic factor deficiency was reported. It was the first identified mutation of GIF in East-Asia and may indicate a new ancestry.